A nanocarbon-coated and nitrogen-doped titanium dioxide material and its preparation method and application

Through nanocarbon coating and nitrogen doping methods, nanocarbon coating and nitrogen doped titanium dioxide materials with spherical structures were prepared, which solved the problem of uneven conductivity of existing titanium dioxide negative electrode materials and significantly improved the conductivity of the material. and cycle stability.

CN116239144BActive Publication Date: 2025-02-18HUADING GUOLIAN SICHUAN BATTERY MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310262983.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-02-18
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

The conductivity of existing titanium dioxide anode materials is uneven, resulting in poor cycle stability and reduced capacity.

Method used

By using nanocarbon coating and nitrogen doping method, nanocarbon coating and nitrogen doping titanium dioxide material with spherical structures was prepared. The method includes mixing a titanium dioxide precursor, a coating agent, a pH adjuster, a dopant, a dispersant and a solvent, and atomizing sintering and secondary carbonization to form a uniform conductive network.

Benefits of technology

It significantly improves the electronic/ion conductivity and cyclic stability of the material, shortens the lithium ion embedding distance, and improves the overall electrochemical performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116239144B_ABST
    Figure CN116239144B_ABST
Patent Text Reader

Abstract

The present invention discloses a nano-carbon coated and nitrogen-doped titanium dioxide material and a preparation method and application thereof, and relates to the field of negative electrode materials for lithium batteries. The method comprises mixing a titanium dioxide precursor, a coating agent, a pH adjusting agent, a dopant, a dispersant and a solvent to obtain a precursor solution; then atomizing the precursor solution to obtain an atomized liquid, passing the atomized liquid into a tubular furnace for a first sintering to obtain a sintered sample; finally, the obtained sintered sample is subjected to a secondary sintering and carbonization to obtain a nano-carbon coated and nitrogen-doped titanium dioxide material. The present invention also provides a nano-carbon coated and nitrogen-doped titanium dioxide material obtained by the above preparation method. The obtained material is a spherical structure with a nanometer size. In the present invention, carbon coating forms a uniform conductive surface, and nitrogen doping increases atomic vacancies, which interact with the carbon layer to form a conductive integrated network, significantly improving the electronic / ionic conductivity and cycle stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium battery negative electrode materials, and specifically relates to a nano-carbon-coated and nitrogen-doped titanium dioxide material and a preparation method and application thereof. Background Art

[0002] In order to improve the comprehensive electrochemical performance of titanium dioxide negative electrode materials, the current mainstream means are through conductive ion doping and amorphous carbon coating. Among them, although the coating technology can effectively improve the cycle stability of titanium dioxide materials, the oxide itself is not conductive, and the uneven coating will lead to uneven conductivity of titanium dioxide negative electrode materials, and the gram capacity will decrease accordingly.

[0003] In order to solve the problem of poor electrochemical performance of titanium dioxide negative electrode, conductive particle doping technology and amorphous carbon coating technology have been developed. Atomic doping is currently mainly achieved by mixing the doping atom precursor with the titanium oxide negative electrode precursor in proportion, sintering it in a reactor, and then achieving atomic doping. Coating technology is to mix the titanium oxide negative electrode material with the coating agent in proportion, and sinter it at a higher temperature to achieve amorphous carbon coating.

[0004] In order to improve the conductivity and cycle stability of titanium dioxide negative electrode materials, a titanium dioxide material with a specific morphology is often prepared by a certain method to optimize one or several structural characteristics of titanium dioxide to achieve its excellent electrochemical performance.

[0005] For example, in order to improve the rate performance of titanium dioxide materials in the prior art, a sol-gel method and subsequent carbonization treatment are used to deposit titanium dioxide on carbon nanotubes to synthesize a tubular titanium dioxide nanotube negative electrode material, which is then sintered to form a carbon coating; the lithium insertion and extraction channel path of the nano-titanium dioxide negative electrode becomes shorter, which improves the lithium insertion efficiency and improves its comprehensive electrochemical performance; thanks to the advantages of the nanotube structure, the comprehensive electrochemical performance is doubled compared with the traditional plate-shaped titanium dioxide negative electrode. The electron microscope image of the obtained nano-tubular titanium dioxide is as follows: Figure 1 Although nano-sized titanium dioxide can shorten the lithium ion insertion and extraction path of the material to improve the rate performance of the battery, the uniformity of the carbon coating of tubular titanium dioxide cannot be guaranteed during gelation, which makes the surface conductivity of the material uneven, resulting in poor cycle stability of the material, and more seriously, it can cause the material to pulverize and cause safety hazards.

[0006] In the prior art, the electron / ion conductivity of titanium dioxide negative electrode materials is low, the polarization is large during the cycle, and the rate performance is poor. In order to solve this problem, the atomic vacancies are increased by doping elements on the surface of titanium dioxide materials, which effectively improves the electron and ion conductivity of titanium dioxide. For example, V is doped into anatase titanium dioxide. 5+ions, which can effectively improve the comprehensive electrochemical performance of the material. This improvement can be attributed to the V 5+ Ions replace Ti 4+ ions and produced more Ti in the lattice 4+ Vacancies. This effect may lead to the generation of more free holes in the doped p-type semiconductor. Therefore, the increase in the hole concentration in the valence band greatly increases the conductivity of the doped sample. However, the element dopants selected by the above technology are mostly divided into solid-phase oxide agents or liquid-phase non-metallic oxides, but these two materials themselves have poor conductivity and do not provide lithium, which will lead to a decrease in the cycle stability and specific capacity of the material.

[0007] In addition, titanium dioxide coating and doping will also bring a series of problems. For example, uneven coating and doping will cause low-valent impurity elements in the transition metal layer to migrate to the lithium layer during the charge and discharge process, occupying lithium vacancies and forming cation mixing. In order to reduce the cation mixing phenomenon, active impurity ions are often introduced into the material to occupy vacancies. At the same time, the specific capacity of the material will be further reduced. Therefore, the existing technology often improves the problems of cation mixing by uniformly doping active elements. Summary of the invention

[0008] The purpose of the present invention is to provide a nano-carbon-coated and nitrogen-doped titanium dioxide material and its preparation method and application. The material has the advantages of small size and spherical structure. The carbon coating forms a uniform conductive surface, while the nitrogen doping increases the atomic vacancies and interacts with the carbon layer to form a conductive integrated network, which significantly improves the electronic / ionic conductivity and cycle stability of the material.

[0009] The present invention first provides a method for preparing a nano-carbon-coated and nitrogen-doped titanium dioxide material, comprising:

[0010] Step 1: mixing a titanium dioxide precursor, a coating agent, a pH adjuster, a dopant, a dispersant and a solvent to obtain a precursor solution;

[0011] Step 2: atomizing the precursor solution obtained in step 1 to obtain an atomized liquid, and passing the atomized liquid into a tube furnace for a first sintering to obtain a sintered sample;

[0012] Step 3: The sintered sample obtained in step 2 is subjected to secondary sintering and carbonization to obtain a nano-carbon-coated and nitrogen-doped titanium dioxide material.

[0013] Preferably, the titanium dioxide precursor in step 1 is tetrabutyl titanate solution or titanium sulfate.

[0014] Preferably, the coating agent in step 1 is citric acid, the pH adjusting agent is acetic acid, the doping agent is urea, the dispersant is PVP, and the solvent is anhydrous ethanol.

[0015] Preferably, the mass ratio of the titanium dioxide precursor, coating agent, pH adjuster, dopant, dispersant and solvent in step 1 is 6:1.5:6.3:0.3:0.1:96.

[0016] Preferably, the mixing described in step 1 is specifically as follows: firstly, the dispersant, the coating agent and the solvent are placed in an ultrasonic disperser for ultrasonic mixing, and then the pH regulator, the titanium dioxide precursor and the dopant are added and ultrasonic dispersion is continued.

[0017] Preferably, the gas flow rate of the atomized liquid in step 2 into the tube furnace is 1-1.5 L / min. Preferably, in step 2, the tube furnace is heated to 500°C at a heating rate of 1-10°C / min in advance, the sintering temperature is 500-550°C, and the sintering time is 0.5-1h.

[0018] Preferably, the temperature of the secondary sintering and carbonization in step three is 500-550° C., the time is 1.5-2 hours, and the protective gas is one of oxygen, nitrogen or argon.

[0019] The present invention also provides a nano-carbon-coated and nitrogen-doped titanium dioxide material obtained by the above preparation method.

[0020] The present invention also provides the use of the nano-carbon-coated and nitrogen-doped titanium dioxide material as a negative electrode in a battery.

[0021] Beneficial effects of the present invention

[0022] The present invention provides a nano-carbon coated and nitrogen-doped titanium dioxide material and its preparation method and application. The method comprises the following steps: mixing a titanium dioxide precursor, a coating agent, a pH adjusting agent, a dopant, a dispersant and a solvent to obtain a precursor solution; then atomizing the precursor solution to obtain an atomized liquid, passing the atomized liquid into a tubular furnace for a first sintering to obtain a sintered sample; finally, the obtained sintered sample is subjected to a secondary sintering and carbonization to obtain a nano-carbon coated and nitrogen-doped titanium dioxide material. Compared with the prior art, the present invention adopts a precursor solvent mixture, and the coating agent and the dopant can be dispersed with the material at the molecular level, and can form a uniform coating layer and dispersed atomic vacancies after drying and molding; and the uniformly coated carbon layer and the N atomic vacancies interact to form a comprehensive conductive network, which significantly improves the electronic / ionic conductivity of the material;

[0023] In addition, the present invention uses a spray drying method to prepare a material that is more uniform and has a spherical structure; regulating the temperature and air intake effectively controls the material size at the nanometer level, can shorten the lithium ion insertion and extraction distance, and further improves the electronic / ionic conductivity of the material.

[0024] The material preparation steps of the present invention are simple, nitrogen doping and carbon coating are completed simultaneously in one step without impurity elements, and there is no need for separate coating, doping, template removal, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0026] Figure 1 This is an electron microscope image of nano-tubular titanium dioxide obtained by the method of the prior art;

[0027] Figure 2 This is a scanning electron microscope photograph of the material prepared in Example 1 of the present invention;

[0028] Figure 3 This is a transmission electron microscope image of the material prepared in Example 1 of the present invention;

[0029] Figure 4 The material prepared in Example 1 of the present invention was -1 ) at a long cycle performance at a current density of . DETAILED DESCRIPTION

[0030] The present invention first provides a method for preparing a nano-carbon-coated and nitrogen-doped titanium dioxide material, comprising:

[0031] Step 1: mixing a titanium dioxide precursor, a coating agent, a pH adjuster, a dopant, a dispersant and a solvent to obtain a precursor solution;

[0032] Step 2: atomizing the precursor solution obtained in step 1 to obtain an atomized liquid, and passing the atomized liquid into a tube furnace for a first sintering to obtain a sintered sample;

[0033] Step 3: The sintered sample obtained in step 2 is subjected to secondary sintering and carbonization to obtain a nano-carbon-coated and nitrogen-doped titanium dioxide material.

[0034] According to the present invention, the preferred order of adding the titanium dioxide precursor, coating agent, pH adjusting agent, dopant, dispersant and solvent is to first put the dispersant, coating agent and solvent into an ultrasonic disperser for ultrasonic mixing, wherein the power of the ultrasonic disperser is preferably 500-800W; the ultrasonic mixing time is preferably 20-30min, and then the pH adjusting agent, titanium dioxide precursor and dopant are added to continue ultrasonic dispersion, and the ultrasonic dispersion time is preferably 1-1.5h.

[0035] According to the present invention, the titanium dioxide precursor is not particularly limited, and the source is commercially available, preferably tetrabutyl titanate solution or titanium sulfate; the coating agent is preferably citric acid, the pH regulator is preferably acetic acid, the dopant is preferably urea, the dispersant is preferably PVP, and the solvent is preferably anhydrous ethanol. The mass ratio (g) of the titanium dioxide precursor, coating agent, pH regulator, dopant, dispersant and solvent is preferably 6:1.5:6.3:0.3:0.1:96; the present invention controls the types and proportions of titanium dioxide precursor, coating agent, pH regulator, dopant, dispersant and solvent, so that the dopant, coating agent and main material are dispersed by molecular agents, and nitrogen doping and carbon coating are completed simultaneously to form a uniform conductive network; the electronic / ionic conductivity of the material is significantly improved, such as the amount of dopant added. If too much is added, tetrabutyl titanate will be hydrolyzed and precipitated, and the precursor solution will fail; if too little is added, the N doping effect is poor.

[0036] According to the present invention, after the precursor solution is obtained, the precursor solution is placed in an atomization instrument, and the atomized liquid is preferably passed into a tubular furnace at a gas flow rate of 1-1.5L / min for sintering. The tubular furnace is heated to 500°C at a heating rate of 1-10°C / min in advance to obtain a once sintered sample; the sintering temperature is preferably 500-550°C, and the sintering time is preferably 0.5-1h.

[0037] According to the present invention, the sample after the first sintering is placed in a tubular furnace for secondary sintering and carbonization. The tubular furnace is heated to 500-550°C at a heating rate of 1-10°C / min, and the protective gas is one of oxygen, nitrogen or argon to obtain a nano-carbon-coated and nitrogen-doped titanium dioxide material. The temperature of the secondary sintering and carbonization is preferably 500-550°C, and the time is preferably 1.5-2h.

[0038] The present invention also provides a nano-carbon-coated and nitrogen-doped titanium dioxide material obtained by the above preparation method. The material is a spherical structure with a nano-scale size ranging from 50 to 500 nm.

[0039] The present invention also provides the use of the nano-carbon-coated and nitrogen-doped titanium dioxide material as a negative electrode in a battery.

[0040] According to the present invention, the nano-carbon-coated and nitrogen-doped titanium dioxide material is used as the negative electrode in detail as follows: the obtained nano-carbon-coated and nitrogen-doped titanium dioxide material is mixed with PVDF and SP in a mass ratio of 7:1:2 or 8:0.5:1.5 and coated on the current collector, and finally made into a CR2016 button battery for testing, and the test voltage is 0-3V.

[0041] The present invention is further described in detail below with reference to specific examples, and the raw materials involved in the examples are all commercially available.

[0042] Example 1

[0043] First, a precursor solution for spray drying was prepared. 0.1 g of polyvinyl pyrrolidone and 1.5 g of citric acid were weighed and uniformly dissolved in 120 mL of anhydrous ethanol solution. After ultrasonic dispersion for half an hour, 6 mL of 98% acetic acid solution was added and stirred evenly. Then, 6 mL of tetrabutyl titanate solution was gradually added, and 0.3 g of urea was added and stirred for half an hour until the solution was clear. During the stirring process, air and water vapor were isolated to prevent hydrolysis of tetrabutyl titanate.

[0044] The uniformly mixed precursor solution was poured into a two-necked flask, and the precursor solution in the two-necked flask was atomized into uniformly dispersed small droplets by an ultrasonic atomizer, and then introduced into a high-temperature tubular reactor at 500°C for sintering at a rate of 1.5L / min by high-purity argon gas, and the sintering time was 0.5;

[0045] During this process, the solvent in the small droplets evaporates rapidly in the high temperature zone, and the solute is deposited on the tube wall at the end of the tube furnace. Since the pyrolysis process in the tube furnace is extremely short, the sample is not evenly decomposed by heat, and there are many defects in the titanium oxide grains, the sample is taken out and sintered at 550℃ for 2h in an argon atmosphere to finally obtain 3.3nm carbon-coated titanium oxide nanospheres.

[0046] Figure 2 This is a scanning electron microscope photo of the material prepared in Example 1 of the present invention. Figure 2 It can be seen that the morphology of the samples is a microsphere structure with a smooth surface. The diameter of the microspheres is distributed between 500nm-2um. They have complete and excellent sphericity and good microsphere dispersion.

[0047] Figure 3 This is a transmission electron microscope image of the material prepared in Example 1 of the present invention. Figure 3 (a) It can be seen that the sample surface is smooth and the sphere is similar to a solid sphere structure. After increasing the transmission resolution, Figure 3 (b) It can be seen that there are extremely fine secondary particles on the surface of the sphere, with a particle size of less than 10nm. Figure 3 (c) It was found that the TiO2 particle size distribution in the sample was between 1-6nm, which verified the calculated data of XRD grains and further demonstrated the lattice of ultrafine anatase TiO2 particles embedded in the carbon matrix. The TiO2 particles were dispersed in the amorphous carbon matrix. This is due to the low spray pyrolysis and calcination temperature, and the amorphous carbon matrix inhibited the growth of TiO2 particles. Due to the fine grain size and the coating of amorphous carbon, the average size of the material was calculated by analyzing the diffraction peaks using the Scherrer formula:

[0048] d=0.9λ / ωcosθ

[0049] Among them, d represents the grain size, λ is the wavelength of X-rays, ω is the half-height width of the strongest diffraction peak, and θ is the diffraction angle. After calculation, the average grain size of the sample is 3.6nm.

[0050] Comparative Example 1

[0051] For electrochemical performance comparison, a spherical titanium dioxide comparison sample was prepared according to the steps and conditions of Example 1, except that the sample taken out of the tube furnace was sintered at 550°C in air for 2 hours to obtain a spherical titanium dioxide comparison sample (ordinary uncoated and undoped sample). Performance data are shown in Figure 1. Figure 4 shown.

[0052] Comparative Example 2

[0053] According to the steps and conditions of Example 1, a spherical titanium dioxide comparative sample was prepared. The difference was that the secondary sintering temperature was increased to 600°C, the secondary structure particles of the obtained material became larger, the coating performance was affected, the material specific capacity was deteriorated, and the overall cycle performance was poor. The specific cycle data are as follows: Figure 4 shown.

[0054] Comparative Example 3

[0055] Spherical titanium dioxide comparative samples were prepared according to the steps and conditions of Example 1, except that the secondary sintering time was changed to 2.5 h. The obtained material particles became larger and the finishing cycle was poor. The specific cycle data are as follows: Figure 4 shown.

[0056] Figure 4 shows the materials of Example 1 and Comparative Examples 1-3 at 2C (0.67A g -1 ) long cycle performance at a current density of . Compared with the ordinary uncoated and doped samples (Comparative Example 1), the carbon-coated and nitrogen-doped titanium dioxide materials have improved initial discharge capacity and discharge capacity after 600 cycles of 2C.

Claims

1. A method for preparing a nanocarbon-coated and nitrogen-doped titanium dioxide material, characterized in that: include: Step 1: mixing a titanium dioxide precursor, a coating agent, a pH adjuster, a dopant, a dispersant and a solvent to obtain a precursor solution; Step 2: Atomizing the precursor solution obtained in step 1 to obtain an atomized liquid, and passing the atomized liquid into a tube furnace for a first sintering to obtain a sintered sample; Step three: The sintered sample obtained in step two is subjected to secondary sintering and carbonization to obtain a nano-carbon-coated and nitrogen-doped titanium dioxide material; Wherein, the temperature of the secondary sintering and carbonization in step 3 is 500-550°C, the time is 1.5-2h, and the protective gas is nitrogen or argon; The coating agent in step one is citric acid, the pH adjusting agent is acetic acid, the doping agent is urea, the dispersing agent is PVP, and the solvent is anhydrous ethanol; the mass ratio of the titanium dioxide precursor, the coating agent, the pH adjusting agent, the doping agent, the dispersing agent and the solvent is 6:1.5:6.3:0.3:0.1:96; in step two, the tubular furnace is heated to 500°C in advance at a heating rate of 1-10°C / min, the sintering temperature is 500-550°C, and the sintering time is 0.5-1h.

2. The method for preparing a nanocarbon-coated and nitrogen-doped titanium dioxide material according to claim 1, characterized in that: The titanium dioxide precursor described in step 1 is tetrabutyl titanate solution or titanium sulfate.

3. The method for preparing a nanocarbon-coated and nitrogen-doped titanium dioxide material according to claim 1, characterized in that: The mixing described in step 1 is specifically as follows: firstly, the dispersant, the coating agent and the solvent are placed in an ultrasonic disperser for ultrasonic mixing, and then the pH regulator, the titanium dioxide precursor and the dopant are added and ultrasonic dispersion is continued.

4. The method for preparing a nanocarbon-coated and nitrogen-doped titanium dioxide material according to claim 1, characterized in that: The flow rate of the atomized liquid in step 2 entering the tube furnace is 1-1.5 L / min.

5. The nano-carbon-coated and nitrogen-doped titanium dioxide material obtained by the preparation method according to any one of claims 1 to 4.

6. Use of the nano-carbon coated and nitrogen-doped titanium dioxide material as claimed in claim 5 as a negative electrode in a battery.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped rutile TiO2 / C negative electrode material for sodium-ion battery

    CN105870447A

  • N-doped TiO2 / C composite material, and preparation method and application thereof

    CN109718823A

  • High-activity titanium dioxide nano-material, and preparation method and application thereof

    CN110385117A